Impact of material shortages to revenue - Stark, Robert J. (University of Wisconsin--Stout, 2019)
The purpose of this study was to determine the role that material shortages played in contributing to decreased actual revenue versus target revenue and to provide a recommendation to improve the material programs that most impacted Company XYZ's ability to achieve the highest possible revenue. By analyzing and organizing data from the Sales, Production, and Material Departments, the material shortages that impacted revenue achievement were identified. Historical data from January 2018 to December 2018 was used as the scope of this study. Monthly revenue goals were aligned with instances of production failures caused by material shortages. A correlation was found between the number of engine shortages that the production line reported and the actualization of monthly sales.
Keywords: Revenue; Production control